Infrastructure and climate change: Impacts and adaptations for the Zambezi River Valley - Paul S. Chinowsky; Amy E. Schweikert; Niko L. Strzepek; Kenneth Strzepek (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
The African Development Bank has called for US40 billion per year over the coming decades to be provided to African countries to address development issues directly related to climate change. The current study addresses a key component of these issues, the effect of climate change on the road infrastructure of Malawi, Mozambique, and Zambia, all located within the Zambezi River Basin. The study incorporates a stressor-response approach to estimate the effects of projected precipitation, temperature, and flooding changes on the paved and unpaved road infrastructure of these countries. The paper highlights the result of running 425 climate scenarios for each road type and policy option from 2010-2050. Based on a resulting database of over 1.4 million data points, the three southern African countries are facing a potential US596 million price tag based on median climate scenarios to maintain and repair roads as a result of damages directly related to temperature and precipitation changes from potential climate change through 2050.
Keywords: Q54; O44; O55; 330; climate change; roads; infrastructure; Mozambique; Malawi; Zambia